PENGEMBANGAN MEDIA E-COMIC SAINS BERBANTUAN COMIC STRIP MAKER PADA MATA PELAJARAN IPAS - Matondang, Khairunnisa; Lidia Simanihuruk; Zainuddin, Zainuddin; Lala Jelita Ananda; Imelda Free Unita Manurung (Jurnal Merah Putih Sekolah Dasar, 2025)
This study aims to develop E-comic learning media assisted by the Comic Strip Maker application for the IPAS subject in Grade IV at SDN 060899 Medan. The research was conducted in response to the low student motivation and learning outcomes, as well as the limited use of innovative learning media at the school. The study employed the 4D development model (Define, Design, Develop, and Disseminate). Data were collected through observations, interviews, expert validation questionnaires, student response questionnaires, and learning outcome tests. The results showed that the developed E-comic media was considered highly feasible by subject matter and media experts, practical based on student responses, and effective in improving learning outcomes based on the analysis of pretest and posttest scores. This media is recommended as an interactive and engaging alternative for science learning.